Efficacy and safety of tacrolimus vs cyclophosphamide in the therapy of patients with idiopathic membranous nephropathy: a meta-analysis - Lin W; Li HY; Lin S; Zhou T (Dove Medical Press, 2019)
Wenshan Lin,*,1 Hong-Yan Li,*,2 Shujun Lin,1 Tianbiao Zhou11Department of Nephrology, The Second Affiliated Hospital of Shantou University Medical College, Shantou, People’s Republic of China; 2Department of Nephrology, Huadu District People’s Hospital of Guangzhou, Southern Medical University, Guangzhou, People’s Republic of China*These authors contributed equally to this workBackground: As one of the therapeutic drugs for idiopathic membranous nephropathy (IMN), tacrolimus (TAC) has not been fully vindicated for its efficacy and tolerability. A meta-analysis was performed to detect the efficacy and safety of TAC plus glucocorticoid vs cyclophosphamide (CTX) plus glucocorticoid in therapy of patients with IMN.Methods: A literature search with a pre-defined search strategy was conducted using English databases (PubMed, EMBASE, ClinicalKey and the Cochrane Library) and Chinese databases (China National Knowledge International, Wanfang, Chinese Scientific Journal Database (VIP)) from inception to Nov 19, 2018. Any high-quality randomized controlled trials (RCTs) comparing the effectiveness or safety of TAC with CTX in IMN patients were included. Data were extracted by two authors independently and analyzed using RevMan 5.3.Results: Four randomized controlled studies were included. In this analysis, we did not find that the statistically significant difference between TAC and CTX groups on 6-month and 12-month treatment complete remission (CR) was evident (6-month: OR=1.53, 95% CI: 0.85–2.76, P=0.15; 12-month: OR=2.17, 95% CI: 0.56–8.44, P=0.27). But TAC had better 6-month total remission (TR; total CR plus partial remission [PR]) than CTX (6-month: OR=2.62, 95% CI: 1.38–4.96, P=0.003; 12-month: OR=1.74, 95% CI: 0.29–10.48, P=0.54), and got a lower proteinuria after 6-month treatment (OR=−0.80, 95% CI: −1.53 to −0.07, P=0.03). TAC had a lower incidence rate on leucopenia than CTX, but had a tendency towards higher blood creatinine. In the meantime, tremor in TAC group was higher than that in CTX group. The differences on other adverse effects such as gastrointestinal syndrome, infection, herpes zoster, hypertension, liver function disorder and hyperglycemia were also analyzed. However, none of them were statistically significant.Conclusion: TAC treatment could get high value of TR and had low value of proteinuria level when compared with those in CTX on 6-month treatment in therapy of patients with IMN.Keywords: tacrolimus, idiopathic membranous nephropathy, complete remission, CR, total remission, TR, meta-analysis